The Shwachman–Bodian–Diamond syndrome gene mutations cause a neonatal form of spondylometaphysial dysplasia (SMD) resembling SMD Sedaghatian type. Issue 4 (30th March 2007) - Nishimura, Gen; Nakashima, Eiji; Hirose, Yuichiro; Cole, Trevor; Cox, Phillip; Cohn, Daniel H; Rimoin, David L; Lachman, Ralph S; Miyamoto, Yoshinari; Kerr, Bronwyn; Unger, Sheila; Ohashi, Hirofumi; et al.
Abstract : The Shwachman–Bodian–Diamond syndrome ( SBDS ) gene is a causative gene for Shwachman–Diamond syndrome, an autosomal recessive disorder with exocrine pancreatic insufficiency, bone marrow dysfunction and skeletal dysplasia. We report here on two patients with skeletal manifestations at the severest end of the phenotypic spectrum of SBDS mutations. An 11-year-old Japanese girl presented with neonatal respiratory failure necessitating lifelong ventilation support, severe short stature and severe developmental delay. She developed neutropenia in infancy, and decreased serum amylase was noted in childhood. A British boy was a stillbirth with pulmonary hypoplasia and hepatic fibrosis found on autopsy. Both cases had neonatal skeletal manifestations that included platyspondyly, lacy iliac crests and severe metaphysial dysplasia, and thus did not fall in the range of the known Shwachman–Diamond syndrome skeletal phenotype but resembled spondylometaphysial dysplasia (SMD) Sedaghatian type. The girl harboured a recurrent mutation (183TA→CT) and a novel missense mutation (79T→C), whereas the boy carried two recurrent mutations (183TA→CT and 258+2T→C). We also examined SBDS in one typical case with SMD Sedaghantian type and eight additional cases with neonatal SMD, but failed to discover SBDS mutations. Our experience expands the phenotypic spectrum of SBDS mutations, which, at its severest end, results in severe neonatal SMD.